2007
DOI: 10.1128/iai.01812-06
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of theLutzomyia longipalpisSalivary Gland Protein Maxadilan on Mouse Macrophages

Abstract: Infection with Leishmania major is enhanced when the sand fly Lutzomyia longipalpis salivary peptide maxadilan (MAX) is injected along with the parasite. Here we determined the effect that MAX has on the secretion of cytokines and nitric oxide (NO) and on parasite survival in macrophages (M⌽s). The cytokines produced by M⌽s can enhance a type 1 response, which will increase NO and the killing of intracellular pathogens such as L. major, or a type 2 response, leading to antibody production that is ineffective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 32 publications
2
43
0
8
Order By: Relevance
“…Morris et al showed increased pathology and parasite burden in a resistant murine strain when MAX was coinoculated with Lm; furthermore, vaccination with MAX resulted in protection against infection (22). In vitro studies have also revealed increased secretion of IL-10 and IL-6 while generally inhibiting TNF-␣ production in macrophages (21,23,24). Such altered cytokine secretion patterns are suggestive of development of a type 2 response shown to increase pathology of Lm infection (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Morris et al showed increased pathology and parasite burden in a resistant murine strain when MAX was coinoculated with Lm; furthermore, vaccination with MAX resulted in protection against infection (22). In vitro studies have also revealed increased secretion of IL-10 and IL-6 while generally inhibiting TNF-␣ production in macrophages (21,23,24). Such altered cytokine secretion patterns are suggestive of development of a type 2 response shown to increase pathology of Lm infection (5).…”
mentioning
confidence: 99%
“…Evidence suggests that salivary molecules have a profound impact on APCs because they have been shown to decrease Ag presentation, NO production, and killing of Lm (9,24). During sand fly feeding, host APCs, including monocytes, macrophages, and dendritic cells (DCs), are exposed to salivary components at the site of inoculation.…”
mentioning
confidence: 99%
“…A great amount of evidence proved the vasoregulatory effect and immunmodulatory properties of maxadilan in non-neurogenic inflammation, which were also shown to be essential for the transmission of Leishmania (Brodie et al, 2007). However, its involvement in neurogenic inflammation has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…longipalpis saliva [48,49]. Furthermore, upon addition of Maxadilan to mouse macrophages in vitro, cytokines associated with Th2 responses including IL-6, IL-10, TGF-β are upregulated; however Th1 cytokines such as IL-12p70 and TNF as well as nitric oxide are downregulated [50]. Maxadilan affects the cells which are important for controlling of Leishmania infection.…”
Section: Sand Fly Saliva and Induction Of Immune Responses And Protecmentioning
confidence: 99%